Upaya Peningkatan hasil Belajar Pendidikan Agama Islam Menggunakan Cooperative Learning Tipe Students Team Achievement Division (STAD) - M Agus Salim (Nazhruna: Jurnal Pendidikan Islam, 2019)
This study is intended to examine efforts to improve student learning outcomes using the STAD type cooperative strategy given the low absorption of students in learning as well as one method for teachers to improve student learning outcomes in schools. Cooperative learning strategies are one way to strive for student activities in learning so that they are involved cognitively and psychomotor in them. But the extent to which this cooperative learning strategy contributes to student learning success compared to the expository strategy needs to be empirically proven. The research method that will be used is Classroom Action Research (CAR)which aims to improve the learning process. The results of this study indicate that learning using cooperative strategies gradually increases from cycle I, II and III with the final percentage score of 88.39. While the implementation of PAI learning using cooperative strategy media also went well, in this case there was an increase in teacher activity during the learning process from cycle I to cycle II, and cycle III. The acquisition of PAI learning achievement increases along with the improvement of learning planning, implementation of learning, and the implementation of evaluation of learning using cooperative strategies.